Additive- and Photocatalyst-Free Borylation of Arylazo Sulfones under Visible Light - Xu, Yuliang; Yang, Xinying; Fang, Hao (Journal of organic chemistry, 2018)
We developed a photocatalyst-free and additive-free, visible light induced borylation reaction using arylazo sulfones as starting material. This protocol shows some advantages such as mild conditions, simple equipment, and wide substrate scope, which gives a complementary protocol for the preparation of arylboronates.